On GARCH(p,q) convergence - Carkovs, J.; Gutmanis, N. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2007)
The paper deals with symmetric GARCH(p,q) model. Assuming that there exists defined by this model stationary time series, we have proposed the necessary and sufficient condition for exponential mean square convergence of any stochastic recurrent procedure satisfying this model to the above stationary time series. A mathematical background of the proposal approach is based on the derived covariance method for mean square exponential stability analysis of linear stochastic difference equations, which permits one to state a mean square convergence criterion for GARCH(p,q) models with any integer positive p and q in the convenient for application form of an integral inequality involving the model parameters. Рассматривается симметричная модель GARCH(p,q). В предположении, что существует задаваемый этой моделью стационарный временной ряд, предлагается необходимое и достаточное условие сходимости в среднем квадратичном любой итерационной процедуры, удовлетворяющей уравнению GARCH(p,q), к этому стационарному процессу. Предложен ковариационный метод анализа линейных разностных уравнений со случайными коэффициентами, который позволил для произвольных целых неотрицательных p и q сформулировать критерий сходимости в среднем квадратичном в удобной для использования форме в виде интегрального неравенства, содержащего параметры модели. Розглядається симетрична модель GARCH(p,q). Припускаючи існування стаціонарного часового ряду, який задається цією моделлю, пропонується необхідна і достатня умова збіжності у середньому квадратичному будь-якої ітераційної процедури, що задовольняє рівнянню GARCH(p,q), до такого стаціонарного процесу. Запропоновано коваріаційний метод аналізу лінійних різницевих рівнянь із випадковими коефіцієнтами, що уможливило для довільних цілих невід’ємних p и q сформулювати критерій збіжності у середньому квадратичному в зручній для використання формі у вигляді інтегральної нерівності із параметрами моделі.